The acute effects of active or passive stretching exercises in swimming as a unique way of warm up before 50m high intensity - Papadimitriou, K.; Tsalis, G.; Loupos, D. (Inquiries in Sport & Physical Education, 2015)
The warm up is essential to participate in sports activities, preparing the body for the upcoming surcharge. Exploring only preheating exercises in athletes are extremely limited. So the aim of the research was to study the acute effects of active or passive stretching exercises in preheating, in the same parts of the body, in 50 meters freestyle swimming. Reaction time (RT) at start, the number of strokes (NS), and the performance (P) of athletes were measured, in the above distance. 16 high level swimmers, 17.0 ± 4.2 years old participated in this study. All swimmers carried out the warm up protocols in a random counterbalanced design. No warm-up (C), active (AS) and passive stretching (PS) protocols were performed without another kind of warm up, in or out of water. According to the study results, the parameters tested (RT, SN & T) did not differ between the three pre-heating conditions in swimmers (p> 0.05). In conclusion, active and passive stretching exercises do not differentiate the return of small distance swimmers as a unique way of warm up, so their use before a speed event is a matter of personal choice of each athlete.